Anti-oxidant and neuro-modulatory effects of bioactive Byttneria pilosa leaf extract in swiss albino mice using behavioral models - Jyoti, Mifta Ahmed; Shah, Md. Shahin; Uddin, Mohammad Najim; Hossain, Mohammed Kamrul; Han, Aixia; Geng, Peiwu; Islam, Mohammad Nazmul; Mamun, Abdullah Al (Frontiers in Chemistry, 2024)
Byttneria pilosa, a flowering plant from the malvaceae family, traditionally used to treat ailments such as boils and scabies, was investigated for its potential health benefits. The study focused on evaluating the antioxidant and anti-diabetic properties in vitro, as well as the in vivo anxiolytic and antidepressant activities of the methanol extract of B. pilosa leaves (MEBP). The study employed various assays to evaluate antioxidant activity, including 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, reducing power capacity, and quantification of total phenolic and flavonoid contents of MEBP. Additionally, anxiolytic and antidepressant activities were evaluated through an elevated plus-maze test (EPMT), light-dark box test (LDBT), forced swimming test (FST), and tail suspension test (TST). The anti-diabetic effect was determined using α-amylase inhibition assay. Docking analysis was performed using BIOVIA and Schrödinger Maestro (v11.1), and the absorption, distribution, metabolism, excretion/toxicity (ADME/T) properties of bioactive substances were investigated utilizing a web-based technique. MEBP exhibited moderate antioxidant activity in DPPH radical scavenging and reducing power capacity assays, with a dose-dependent response. The total phenolic and flavonoid content measured were 70±1.53 mg and 22.33±1.20 mg, respectively. It demonstrated significant effects in α-amylase inhibition, comparable to acarbose. In behavioral tests, MEBP dose-dependently altered time spent in open arms/lightbox and closed arms/dark box, indicating anxiolytic effects. Moreover, MEBP significantly reduced immobility duration in FST and TST, suggesting antidepressant properties. Molecular docking analysis revealed favorable interactions between beta-sitosterol and specific targets, suggesting potential mediation of anxiolytic and antidiabetic effects. Overall, MEBP exhibits notable anxiolytic and antidepressant properties, along with moderate antioxidant and anti-diabetic activities.